2019
DOI: 10.1111/srt.12697
|View full text |Cite
|
Sign up to set email alerts
|

Development of the multispectral UV polarization reflectance imaging system (MUPRIS) for in situ monitoring of the UV protection efficacy of sunscreen on human skin

Abstract: BackgroundProtection of the human skin from ultraviolet (UV) damage is one of the main issues in dermatology and cosmetology. The UV protection efficacy (UVPE) of the sunscreen film is decreased by sweat, sebum, and friction during the day. However, the technical relationship between the UVPE evaluated in a laboratory and the actual protection in daily use has not been clarified, because the UVPE measurement method in real‐life setting has not been established. This study aimed to develop a novel UVPE evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…14 Importantly, multispectral imaging enabled data to be acquired over a large wavelength span, with full coverage of the HEV band. The use of multispectral cameras has been recently been evaluated for a range of applications, including in proposed methods for the determination of a UV photoprotection index and for measuring UV protection efficacy from multispectral reflectance, 15 and for characterising erythema zones after photo-exposure for calculating SPFs for sunscreens (European patent: WO 2020/148454). 16 Another advantage of the multispectral imaging technique is that the reflectance images can be used to visualize how evenly sunscreens have been spread during application.…”
Section: Discussionmentioning
confidence: 99%
“…14 Importantly, multispectral imaging enabled data to be acquired over a large wavelength span, with full coverage of the HEV band. The use of multispectral cameras has been recently been evaluated for a range of applications, including in proposed methods for the determination of a UV photoprotection index and for measuring UV protection efficacy from multispectral reflectance, 15 and for characterising erythema zones after photo-exposure for calculating SPFs for sunscreens (European patent: WO 2020/148454). 16 Another advantage of the multispectral imaging technique is that the reflectance images can be used to visualize how evenly sunscreens have been spread during application.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently some sunscreens are available which protect our skin immediately against UV radiation. Recent studies showed that sunscreen can remain on our skin at its desired SPF for as long as 8 hours and reapplication is suggested, if the sunscreen is removed by sweating, friction, water immersion (15). Spray sunscreens are less popular than the cream-based sunscreen because the wind can disperse the sunscreen, resulting in inadequate application and aerosolized sunscreens are flammable.…”
Section: Methods Of Application Of Sunscreenmentioning
confidence: 99%
“…The technique has already been evaluated as a potential method for carrying out noninvasive analysis of the skin for applications such as erythema characterization 14 and SPF measurement. 15 The aim of the current study was to determine if multispectral imaging could be used as a reliable and rapid technique for assessing the real dose of an SPF 50+ sunscreen applied to the face of healthy volunteers, and evaluate the impact of providing application instructions or reapplying the sunscreen on the amount of sunscreen applied and the heterogeneity of the application across different areas of the face.…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral imaging is a versatile technique that permits the acquisition of reflectance images of the skin at specific wavelengths. The technique has already been evaluated as a potential method for carrying out noninvasive analysis of the skin for applications such as erythema characterization 14 and SPF measurement 15 …”
Section: Introductionmentioning
confidence: 99%